(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
India is a developing country, and in a developing country Micro Small and Medium (MSME) are accepted as the “engine of economic growth in India”. In recent years MSME have gained attention of policy makers all around the country because of its true capacity creating enormous measure of result from a lower venture it required. This work concentrated area has the limit of lessening provincial awkwardness through pay and business age. Financial development of provincial people and helps in manageable turn of events.MSME sector is very heterogeneous in nature in India. This research paper will focus the existing trends and scenario of MSME in India.